Erpangir Ku Lau Ritual: Between Religion and Identity - Vanesia Amelia Sebayang; Asmyta Surbakti; Torang Naiborhu (International Journal of Interreligious and Intercultural Studies, 2022)
Erpangir ku lau is a ritual of the Karo people based on old religion called Pemena, as a medium for self-cleaning to maintain the sanctity of the body and spirit of a human being. Humans who have been physically and spiritually clean are having been kept away from evil inflences so that they are worthy of getting closer to their ancestors, the universe’s spirit, andalso God. However, while Christianity zending is carried out by the Dutch missionary unionin Tanah Karo in 1890-1904, all of the traditional customary and cultural practices towards ancestor and God were prohibited to be done. The Dutch aiming to change the Karo people’s perception of their own cultural identity. Nowadays, The Karo people divided into several groups, each with their understanding of the cultural customs of their ancestors, including the erpangir ku lau. This research uses a qualitative descriptive research method. The theories used are deconstruction and postcolonial theory. The results of this research were erpangir ku lau is a human ways to communicate with their God while maintaining a harmonious relationship between humans, the universe, and their ancestors. It has been proven that erpangir ku lau ritual is black magic worship was fully a colonial construction. Erpangir ku lau is a root that shapes the identity of the Karo people, known as metami, melias, mehamat, perkuah, and perkeleng. Even though they were no longer adhere to ancestral beliefs, the Karo people should reinterpret the identity-forming moral values contained in the erpangir ku lau ritual and then attach them side by side with whatever beliefs they currently hold.